NIRS Database on fresh blended yellow cassava for DM, HCN, TCC, TBC & cooking time at CIAT, Colombia - Tran, Thierry; Belalcazar Martinez, John Eiver (2023)
The database contains biophysical data (DM, HCN, TCC, TBC, cooking time) and NIRS data of 1056 samples of biofortified (yellow) cassava harvested at CIAT over several years (2016-2019). NIRS data was recorded on fresh blended cassava roots, using a Foss 6500 instrument. The objective of the study is to investigate correlations between biophysical data and NIRS data, using different statistical approaches to identify the one(s) that works best. Deep learning algorithms will also be tested to assess their potential for more accurate NIRS calibrations. (2020-7-12)